OBSERVATION ON THE PARASITES AND ASSOCIATES OF WOOD BORING MOLLUSCS AND CRUSTACEANS OF THE SOUTH - WEST COAST OF INDIA - SANTHAKUMARI, V; NAIR, N BALAKRISHNAN (Fishery Technology, 2017)
An interesting assemblage of commensalic organisms ranging from Protozoa to Arthropoda have been identified from the wood boring animals from the south-west coast of India. Certain aspects of the general biology of the associated ciliates such as the nature of incidence, division in relation to environmental parameters, survival outside the body of the host and reactions related to the general condition of the host are described. Results are also presented of the tolerance of the rare conunensalic hydroid Eutima commensalis to different salinities of the medium.